Determinan Pekerja Anak Sektor Perkebunan di Provinsi Sumatera Utara - Izzati, Fatikha Maulida; Sitorus, Jeffry R. H. (Seminar Nasional Official Statistics, 2023)
Child labor is a violation of child protection rights, especially if working in the worst forms of child labor, one of which is in the plantation sector that occurs in North Sumatra. The purpose of this study is to determine the general description and factors that significantly affect child labor in the plantation sector in North Sumatra. The unit of analysis is the labor of children aged 10-17 years who have not head of household status in North Sumatra sourced from Susenas Kor in March 2021. The analysis method used is descriptive analysis and multilevel logistic regression which is divided into two levels. The results of this study show that the working age of children is 10-12 years, not in school, and the number of household members is more than four, and the percentage of poor people at the district / city level has a greater tendency to work in the plantation sector. Meanwhile, child laborers from households with land assets and open unemployment rates in districts are less likely to work in the plantation sector.